A review on the production of nitrogen-containing compounds from microalgal biomass via pyrolysis. (December 2018) - Yu, Jianglong; Maliutina, Kristina; Tahmasebi, Arash
Highlights: Nitrogen-containing compounds (NCCs) are valuable products of microalgae pyrolysis. Major pyrolysis techniques for the production of NCCs are systematically reviewed. The transformation of nitrogen is associated with the formation of NCCs. Measures to increase the selectivity of NCCs are suggested. Future research needs are identified. Abstract: Nitrogen-containing compounds (NCCs) which may be produced from nitrogen-rich biomass such as microalgae, may find important biochemical and biomedical applications. This review summarizes the recent knowledge about the formation mechanism of NCCs during pyrolysis of microalgae. The key technical and biological aspects of microalgae and pyrolysis process parameters, which influence the formation of NCCs, have been analyzed. The mechanism of formation of NCCs such as indole, pyridine, amides, and nitriles during primary and secondary pyrolysis reactions are elaborated. It has been emphasized that the pyrolysis conditions and the use of catalysts had significant impacts on the yields and compositions of NCCs. The available information shows that the transformation of nitrogen and nitrogen functionalities during pyrolysis are strongly associated with the formation process of NCCs. The challenges in the development of pyrolysis technologies for the production of NCCs from microalgae are identified with future research needs identified.